The Influence of Internal Factors of Utilization of Posyandu Toddlers in the Working Area of the Sipiongot Health Center, Padang Lawas Utara Regency - Elli Diana Siregar; Anto J. Hadi; Alprida Harahap; Haslinah Ahmad (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: Posyandu is an important means of disease prevention and monitoring of the growth of toddlers. However, the level of community participation in Posyandu still varies, which is allegedly influenced by several internal factors. Objective: This study aims to analyze the influence of internal factors on the utilization of Posyandu for toddlers in the working area of the Sipiongot Health Center, Padang Lawas Utara Regency. Methods: This study used a cross-sectional study design on mothers under five who used Posyandu Madya and Purnama services in the working area of the Sipiongot Health Center. The sample was taken by accidental sampling technique for 60 days, involving 81 mothers under five. Data was collected through a questionnaire distributed to mothers of toddlers who came to the Posyandu. Data analysis was carried out using the chi-square method and logistic regression. Results: This study showed that internal factors such as education (p = 0.001), occupation (p = 0.001), and knowledge (p = 0.001) had a positive relationship with the utilization of Posyandu for toddlers. Of the three variables, knowledge shows the strongest influence on the utilization of Posyandu with an Exp(B) = 15.312 value. Conclusion: Internal factors have an important role in encouraging the use of Posyandu for toddlers. Therefore, increasing public knowledge and awareness about the benefits of Posyandu is urgently needed to ensure the optimization of sustainable health services for toddlers.